Doing sport is good – Responsible for popularization of sport - Ráthonyi-Odor, Kinga; Rátonyi, Gergely; Borély, Attila (Acta Agraria Debreceniensis, 2016)
Responsible leaders of more and more companies build legal, ethic, moral, environmental and social aspects in their goals and values beyond profit maximization. The number of companies whose activities in terms of social responsibility (CSR) has clear connections with promoting and putting forward sports shows an increasing tendency. The aim of this study is the conceptual clarification of corporate social responsibility, and emphasize the CSR’s significance in sport management, next the analysis of 3 top food and beverage companies’ (Coca-Cola, Nestle, Danone) CSR activity in special regard to sport management in Hungary and abroad.